'End of life could be on any ward really': A qualitative study of hospital volunteers' end-of-life care training needs and learning preferences. (October 2017) - Brighton, Lisa Jane; Koffman, Jonathan; Robinson, Vicky; Khan, Shaheen A; George, Rob; Burman, Rachel; Selman, Lucy Ellen
Background: Over half of all deaths in Europe occur in hospital, a location associated with many complaints. Initiatives to improve inpatient end-of-life care are therefore a priority. In England, over 78, 000 volunteers provide a potentially cost-effective resource to hospitals. Many work with people who are dying and their families, yet little is known about their training in end-of-life care. Aims: To explore hospital volunteers' end-of-life care training needs and learning preferences, and the acceptability of training evaluation methods. Design: Qualitative focus groups. Setting/participants: Volunteers from a large teaching hospital were purposively sampled. Results: Five focus groups were conducted with 25 hospital volunteers (aged 19–80 years). Four themes emerged as follows: preparation for the volunteering role, training needs, training preferences and evaluation preferences. Many described encounters with patients with life-threatening illness and their families. Perceived training needs in end-of-life care included communication skills, grief and bereavement, spiritual diversity, common symptoms, and self-care. Volunteers valued learning from peers and end-of-life care specialists using interactive teaching methods including real-case examples and role plays. A chance to 'refresh' training at a later date was suggested to enhance learning. Evaluation through self-reports or observations were acceptable, but ratings by patients, families and staff were thought to be pragmatically unsuitable owing to sporadic contact with each. Conclusion: Gaps in end-of-life care training for hospital volunteers indicate scope to maximise on this resource. This evidence will inform development of training and evaluations which could better enable volunteers to make positive, cost-effective contributions to end-of-life care in hospitals.